Why do forest products become less available?: A pan-tropical comparison of drivers of forest-resource degradation - Hermans-Neumann, Kathleen; Gerstner, K.; Geijzendorffer, I.R.; Herold, Martin; Seppelt, Ralf; Wunder, Sven (IOP Publishing, 2016)
Forest products provide an important source of income and wellbeing for rural smallholder communities across the tropics. Although tropical forest products frequently become over-exploited, only few studies explicitly address the dynamics of degradation in response to socio-economic drivers. Our study addresses this gap by analyzing the factors driving changes in tropical forest products in the perception of rural smallholder communities. Using the poverty and environment network global dataset, we studied recently perceived trends of forest product availability considering firewood, charcoal, timber, food, medicine, forage and other forest products. We looked at a pan-tropical sample of 233 villages with forest access. Our results show that 90% of the villages experienced declining availability of forest resources over the last five years according to the informants. Timber and fuelwood together with forest foods were featured as the most strongly affected, though with marked differences across continents. In contrast, availability of at least one main forest product was perceived to increase in only 39% of the villages. Furthermore, the growing local use of forest resources is seen as the main culprit for the decline. In villages with both growing forest resource use and immigration—vividly illustrating demographic pressures—the strongest forest resources degradation was observed. Conversely, villages with little or no population growth and a decreased use of forest resources were most likely to see significant forest-resource increases. Further, villages are less likely to perceive resource declines when local communities own a significant share of forest area. Our results thus suggest that perceived resource declines have only exceptionally triggered adaptations in local resource-use and management patterns that would effectively deal with scarcity. Hence, at the margin this supports neo-Malthusian over neo-Boserupian explanations of local resource-use dynamics.